ANALISIS PERILAKU AGRESIF PADA SISWA KELAS X SMA MUHAMMADIYAH 1 PONTIANAK - Anggi Susanti; Luhur Wicaksono; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThis research generally purposed to obtained the description about “Students’ Aggressive Behaviour in Class X of SMA Muhammadiyah 1 Pontianak’’. (1) The form of students’ aggressive behaviour in class X of SMA Muhammadiyah 1 Pontianak. (2) The factor affects students’ aggressive behaviour in class X of SMA Muhammadiyah 1 Pontianak. (3) The counselling teacher’s support in handling students’ aggressive behaviour in class X of SMA Muhammadiyah 1 Pontianak. The method used was descriptive in the survey-study form of research. The research subject was five students with aggressive behaviour and their close friends, the parent of one of the students with aggressive behaviour, and a counselling teacher. The qualitative approach was used in this research. The technique of data collection was observation, interview, documentation, and home-visit. Based on the research, the types of aggressive behaviour in verbal and nonverbal are (1) Shouting, (2) Cursing, (3) Teasing, (4) Hitting, (5) Kicking, (6) Slapping, (7) Destructing, (8) Biting. The factors affect students’ aggressive behaviour internally are (1) Genetics, (2) Emotions, (3) Anger, (4) Family Environment, (5) Social Environment, (6) School Environment.Keywords: Aggressive, Behaviour, External, Internal, Nonverbal, Verbal